Don Hermógenes Miranda: un curandero llamado Pato Pinto - Molina Loza, Carlos Arturo (1984)
The present article consists of two parts, one in which the healer tells us about his life and his work. And a second one in which the author makes a brief analysis explaining the reason for the effectiveness of the healer's intervention. The material was collected during a visit in December 1983 and January 1984. The healer's speech was recorded and presented, except for one rearrangement, without any modification.